Bibliometric Analysis of the Role of Culture in Sustainable Development - Loso Judijanto; Tera Lesmana; Salwa Aulia Novitasari (Westscience Press, 2024)
The intricate relationship between culture and sustainable development has emerged as a focal point of scholarly inquiry and policy discourse in an era marked by increasing globalization and interconnectedness. Culture, encompassing beliefs, values, customs, traditions, and social norms, plays a fundamental role in shaping individuals' perceptions, behaviors, and interactions with the environment. However, the nuanced influence of culture on sustainable development remains underexplored, leading to fragmented literature and disparate thematic focuses. To address this gap, this research conducts a comprehensive bibliometric analysis to elucidate the multifaceted role of culture in sustainable development. Through the identification of key thematic areas, trends, and patterns within the existing literature, this study aims to pinpoint gaps and emerging areas of interest for future research endeavors. The insights gleaned from this analysis can inform evidence-based policymaking and contribute to the development of inclusive, culturally sensitive approaches to sustainable development.